(untitled) (Materiali di Estetica. Terza serie, 2020)
In his studies on Leonardo, Antonio Banfi emphasized how the dimension of studying technique constitutes a privileged reality within the work of Leonardo da Vinci. In this context, Leonardo devoted so much space to mechanics and mathematics, coming to understand how the investigation of nature requires a new approach and a new abstraction. The relationship between art and science was thus configured in Leonardo as a new cultural and civil paradigm that still today constitutes a progressive reference program.